Telehealth in cardiac rehabilitation: a review of current applications and future prospects for practical use - O. V. Kamenskaya; I. Yu. Loginova; A. S. Klinkova; A. R. Tarkova; R. A. Naydenov; E. I. Kretov; V. V. Lomivorotov (Российский кардиологический журнал, 2020)
The article provides an overview of actual studies on cardiac rehabilitation using telehealth technologies, presents the types of telerehabilitation in clinical practice. The physiological mechanisms of exercise effects in rehabilitation programs in cardiovascular patients are considered in most detail. Telerehabilitation areas with potential for further study are presented.